-2(y-3)=4(y+3)

Simple and best practice solution for -2(y-3)=4(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(y-3)=4(y+3) equation:


Simplifying
-2(y + -3) = 4(y + 3)

Reorder the terms:
-2(-3 + y) = 4(y + 3)
(-3 * -2 + y * -2) = 4(y + 3)
(6 + -2y) = 4(y + 3)

Reorder the terms:
6 + -2y = 4(3 + y)
6 + -2y = (3 * 4 + y * 4)
6 + -2y = (12 + 4y)

Solving
6 + -2y = 12 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
6 + -2y + -4y = 12 + 4y + -4y

Combine like terms: -2y + -4y = -6y
6 + -6y = 12 + 4y + -4y

Combine like terms: 4y + -4y = 0
6 + -6y = 12 + 0
6 + -6y = 12

Add '-6' to each side of the equation.
6 + -6 + -6y = 12 + -6

Combine like terms: 6 + -6 = 0
0 + -6y = 12 + -6
-6y = 12 + -6

Combine like terms: 12 + -6 = 6
-6y = 6

Divide each side by '-6'.
y = -1

Simplifying
y = -1

See similar equations:

| 2m+-6=7 | | 4/2=x | | 4x^2-15x+13=-3x+8 | | 8x^2-5x-7=2 | | 6x^2+25=-25x | | 2w+1=w | | 10h+8=10 | | 5x+10=2x+10 | | 51-4x=14x+17 | | 222-7x=38x+17 | | x^2+6x=x+14 | | 8-9x=108-37x | | 115-5x=5x+11 | | -3+4x^2=2 | | -137-10x=7x+16 | | 2b^2-9=12b | | 3x^2-x^2=10 | | (x+2)(2x+5)=36 | | 9x^4-8x^2-1=0 | | 14=3x-35 | | 2x+4=340 | | (6x^2-5x)(6x^2+5x)= | | -56=-6x+4 | | 4x^2-2=1 | | 7+9r+10k-5r-3k-24= | | (6x^2-5x)(6x^2+5)= | | 150+30(x+2.50)=500 | | x^2+18x-175=0 | | 3(2y-1)= | | 3g-1=2g+8 | | z^2=6z-2 | | 2x-5=10-69 |

Equations solver categories